Combination of geophysical and hydrogeological data to explain contradictions between infiltration and atmospheric precipitation - Shevchenko, O.; Bublyas, V.; Oshurok, D. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
A traditional and non-standard approach to the analysis of estimated values of groundwater infiltration feeding using the charge sign of the electric field of the surface atmosphere is considered. A comparison of the results of hydrogeological calculations and observations from specific electrophysical and meteorological factors made it possible to explain the discrepancies between the values of infiltration nutrition and the amount of precipitation. The daily values of groundwater recharge were determined based on 41-year observations in wells in the city Khmelnyk. The average long-term value of infiltration recharge of groundwater from GWT 0.8–2.3 m was 145 mm, from GWT 2.7–4.5 m – 14.7 mm (fluctuations in the range from 129 mm to negative values). A significant correlation between the annual values of infiltration and precipitation at GWT0.8–2.3 m was observed only at the first stage of observations (1980–1988). However, there are also significant contradictions in the ratios of infiltration and precipitation, which could be explained only by involving the data of our own electrophysical observations. For the period from 2008 to 2017, the negative values of the "infiltration-temperature" correlation coefficients for the summer season changed to positive ones, which suggests an increase in the importance of moisture transfer mechanisms in the form of steam. Data on the charge sign of the static electric field of the surface layer of the atmosphere support this conclusion. At high values of the intensity of the static electric field (E) with a negative sign, the direction of moisture movement has an upward character, thanks to which evaporation from the aeration zone increases several times compared to what happens at zero values of E. And the intensity of the electric field with a positive sign forms a downward movement of moisture, which leads to an increase of GWT. From this, the cases when low values of infiltration nutrition were obtained with a significant amount of precipitation become more understandable. Conversely, the low amount of precipitation in 2014–2017 (average value 524 mm) was accompanied by high groundwater recharge (160 mm – 10 % above the norm), stable underground flow to the river in the range of 90–100 m3 /year/m and by the growth of GWT due to the positive values of the static electric field and the decrease in wind strength. This electrical factor has such a powerful influence that it is able to neutralize and effectively counteract the negative impact on groundwater recharge of temperature rise and air humidity deficiency. Since electrodynamic processes have a significant and sometimes decisive role not only in moisture transport in the aeration zone, but also in regional processes of groundwater feeding, the creation of artificial positively charged static fields above the soil surface can become the most effective safeguard against the depletion of groundwater reserves during hydrogeological drought.
Keywords: infiltration; supply; unloading; groundwater levels; regime; temperature; precipitation; balance; аeration zone; electrodynamics